Points de vue et créations paysagères. Être un paysan agroforestier - Olivier Bories; Jean-Pascal Fontorbes; Anne-Marie Granié (EchoGéo)
Agroforestry rehabilitates countryside denuded by the spread of plots. It puts lines of trees back into the country and plays with its effects of rows, contours and outlines to create surprise in the landscape. We went with the camera into these tree-striped fields. For a year we met and filmed agroforestry farmers. Five. In Auriac-sur-Vendinelle, Caubiac and Fontenilles in Haute-Garonne, Noilhan and Auch in the Gers. This article presents the results of our filmic research and puts our images and sounds into words. It talks about emotions, agroforestry landscapes, and about the people who discreetly write who they are in the territory by planting trees in their plots. We filmed their gestures as a silent agroforestry word. We discovered that in these lines of trees, the agroforesters are building a path of sustainable thought and agro-ecological practices, a relationship with the world.